Social Integration Through Sport in a Cross-Cultural Setting : Stories from Refugees Living in Central Finland - Moyo, Langa (2018)
Finland has rapidly become a desirable and popular destination for migrants and refugees seeking a better life fleeing from factors of societal discrimination, inequalities and oppressive regimes. In the advent of the prevailing situation of the migration of people from war-affected regions around the world, the research conducted in this paper aims at demonstrating the key concepts and processes through which participation in sport can contribute to refugees’ bonding, bridging, linking and enhancing their social capital in society. The purpose of this study is to identify the role that sport plays in the social integration of refugees living in a diverse cultural setting in the Central Finland region. Five research participants, between the ages of 19-53, emphasize the significance of the concept for facilitating the development of interlinking social issues of the host nation and refugee immigrants, with the emphasis on the refugees themselves. Qualitative methodologies, primarily participant observations and semi-structured interviews, are applied in the five cases that illustrate how sport can have various meanings for young and old people alike. It may work in building social contacts within a sport club setting (Anup’s story), but also highlights accessibility issues (Ahmed’s story). It can define one’s wish not to maintain their cultural identity (Sami’s story), can become a way of life through civic participation (Anwar’s story), and can reinforce aspirations of return migration (Issa’s story). All five cases, however, highlight how sport provides the respective individuals with a platform for socialization and cultural expression in attaining social capital. Despite there being a language barrier in the initial stages of the integration process, their involvement or participation in sport is what matters, and previous research has shown that people from ethnic minority backgrounds value positive social interactions, while also contributing to their local community in an affirming and meaningful way.